Determination of Firing Solution Settings for Engagement of UAVs by a Man-Portable Counter-UAV System - Łukasz SZMIT; Grzegorz LEŚNIK (Problemy Mechatroniki)
The paper presents the operating principle of the Man-Portable Counter Miniature Unmanned Aerial Vehicles System (MPC-MUAVS), with particular reference to the development of its firing solution settings and the methodology and structure of development of the firing tables implemented in the ballistic calculator of the MPC-MUAVS. This ballistic calculator has been applied in the MPC-MUAVS targeting sight assembly, while the entire MPC-MUAVS is intended to counter UAVs within 50 m of the MPC-MUAVS operator. The MPC-MUAVS is being developed under project DOB-1P/02/18/2016, funded by the Polish National Centre for Research and Development.